2006
DOI: 10.1063/1.2172230
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of pinning centers in ferroelectrics

Abstract: We present a direct observation of nanoscale ferroelectric domain pinning centers in lithium niobate crystals. A high-voltage atomic force microscope has been used to tailor nanodomain structures in LiNbO3 crystal with high defect concentration. Domain pinning and depinning events have been captured following thermally induced domain decay process. The pinning centers’ influence on the domain wall dynamics has been analyzed by comparing domain growth in stoichiometric and congruent LiNbO3 crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…33 Most recently, Agronin et al have observed domain pinning on structural defects. 34 The primary limitation of these studies of domain growth is the large time required to perform multiple switching and imaging steps. Moreover, the information is obtained on the domain growth initiated at a single point for different bias conditions, thus precluding systematic studies of microstructure influence on domain growth process.…”
Section: Current Results On Nanoscale Polarization Dynamicsmentioning
confidence: 99%
“…33 Most recently, Agronin et al have observed domain pinning on structural defects. 34 The primary limitation of these studies of domain growth is the large time required to perform multiple switching and imaging steps. Moreover, the information is obtained on the domain growth initiated at a single point for different bias conditions, thus precluding systematic studies of microstructure influence on domain growth process.…”
Section: Current Results On Nanoscale Polarization Dynamicsmentioning
confidence: 99%
“…4,5 Subsequent imaging of the switched domain provides direct insight into domain growth mechanism 6 and relaxation kinetics 7 , from which the effect of macroscopic defects, 8 microscopic disorder, 9 and surface state on domain wall dynamics and pinning can be established. The primary limitation of this approach is the (a) uncontrollable effect of surface charge migration 10,11 inevitable in ambient conditions on observed growth and relaxation kinetics, and (b) extremely large times (~10s -hours) required for studies even at a single location.…”
mentioning
confidence: 99%
“…[11][12][13][14] In these, a square region was uniformly poled by −8 V, and pulses of opposite polarity were applied at several locations near the GB. Topographic and piezoelectric images obtained after pulses of 7 V for 10 s and 8 V for 3, 15, and 20 s have been applied are shown in Figs.…”
mentioning
confidence: 99%